Lithium battery electrolyte for reducing lithium metal negative electrode polarization phenomenon and preparation method and application thereof

CN122931035APending Publication Date: 2026-10-16NORTHWESTERN POLYTECHNICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611053441.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-15
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]本发明的目的在于提供一种降低锂金属负极极化现象并提高锂金属负极电化学性能的锂电池电解液及其制备方法与应用,通过使用富相染料分子添加剂,以解决锂金属负极易与电解液发生副反应、界面失稳、锂沉积不均和极化电压增大的系列问题

Benefits of technology

[0016]This invention utilizes a phase-rich additive composed of phenothiazine and azobenzenesulfonic acid molecules. In the electrolyte, positively charged phenothiazine cationic dye molecules and negatively charged azobenzenesulfonic acid anionic dye molecules form an "ion-pair adsorption layer" structure through electrostatic attraction. This ionic structure reduces the self-charge repulsion of the molecules, allowing them to co-adsorb more tightly and orderly onto the lithium anode surface, thus constructing a denser physical barrier. Compared to single-phase dye molecule additives, the co-adsorption-formed mixed adsorption layer is denser and more ordered than a single component, and can more effectively isolate the electrolyte from direct contact with lithium metal, suppressing side reactions and significantly reducing the interfacial polarization voltage. Simultaneously, the phase-rich dye ion-pair structure alters the solvation environment around lithium ions, providing multiple sites for ion desolvation, synergistically reducing the desolvation barrier, homogenizing the interfacial electric field, and resulting in a more uniform current density distribution on the electrode surface. Furthermore, this ion-pair structure can promote lithium salt dissociation and ion transport. The polar groups in the compound additives can interact with lithium salt anions, promoting lithium salt dissociation, promoting the dissociation of electrolyte cations and anions, and increasing the migration rate of lithium ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122931035A_ABST
    Figure CN122931035A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of lithium battery electrolyte, and discloses a lithium battery electrolyte for reducing lithium metal negative electrode polarization, a preparation method and application thereof. The electrolyte comprises a lithium salt, an ether or ester organic solvent and a rich-phase (phenothiazine group + azobenzene sulfonic acid group) dye molecule additive, the additive content is 0.25-2.0 mg / mL ‑1 , preferably methylene blue + methyl orange (molar ratio 1:1). The rich-phase dye molecule can form a dense adsorption layer of cation and anion structures on the lithium metal surface through electrostatic attraction and co-adsorption, reshape the inner Helmholtz layer near the negative electrode surface, reduce the direct contact of the solvent with the lithium metal, promote the desolvation process of lithium ions, and promote the uniform deposition of lithium through the dense physical barrier and lithiumophilic adsorption, so that the lithium metal negative electrode polarization is reduced, and the lithium negative electrode utilization efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of lithium battery electrolytes, lithium metal batteries and electrochemical energy storage devices, specifically to a lithium battery electrolyte that reduces the polarization phenomenon of lithium metal negative electrode, its preparation method and application. Background Technology

[0002] With the development of portable electronic devices, electric vehicles, and other high-energy-density electrical components, the requirements for energy density and service life of lithium batteries continue to increase. The theoretical capacity of graphite anodes is 372 mAh g⁻¹. -1 The energy density of traditional lithium-ion batteries using graphite as the anode material is gradually approaching its theoretical upper limit; the theoretical capacity of lithium metal anodes is 3860 mAhg. -1 The energy density of lithium metal anodes is significantly higher than that of graphite anodes, making their use a crucial direction for improving lithium-ion battery energy density. However, lithium metal anodes have extremely low electrochemical potentials, making them prone to irreversible side reactions with the electrolyte, leading to anode corrosion and interfacial instability. During lithium metal deposition / stripping, the repeated breakage and regeneration of the solid electrolyte mesophase on the anode surface continuously consumes active lithium and electrolyte components, inducing uneven lithium deposition, dendrite growth, and increased interfacial impedance. These processes result in reduced anode utilization efficiency, limited battery energy output, and manifested as increased polarization voltage and decreased cycle life.

[0003] To address the stability and polarization issues of lithium metal anode interfaces, regulating the anode interface through electrolyte additives is a low-cost method with good process compatibility. If the additives can preferentially adsorb on the lithium metal surface and form an effective interface layer, it is expected to reduce direct contact between the solvent and lithium metal, suppress side reactions, and promote uniform lithium ion deposition.

[0004] Therefore, developing an electrolyte additive system with low content, suitable for ether and ester electrolyte systems, and capable of reducing lithium metal anode polarization has practical application value. Summary of the Invention

[0005] The purpose of this invention is to provide a lithium battery electrolyte that reduces lithium metal anode polarization and improves the electrochemical performance of the lithium metal anode, along with its preparation method and applications. This is achieved by using a phase-rich dye molecule additive to address a series of problems related to lithium metal anodes, including side reactions with the electrolyte, interfacial instability, uneven lithium deposition, and increased polarization voltage. Specifically, the phase-rich dye molecules can form a dense molecular adsorption layer with anionic and cationic structures on the lithium metal surface through electrostatic attraction and co-adsorption, reshaping the inner Helmholtz layer near the anode surface, reducing direct contact between the solvent and lithium metal, promoting the desolvation process of lithium ions, and promoting uniform lithium deposition through dense physical barriers and lithiophilic adsorption. This reduces lithium metal anode polarization and improves the utilization efficiency of the lithium anode.

[0006] To achieve the above objectives, in a first aspect, the present invention provides a lithium battery electrolyte for reducing lithium metal anode polarization, comprising a lithium salt, a solvent, and a solution in a concentration of 0.25-2.0 mg / mL. -1 A phase-rich dye additive used to reduce the polarization phenomenon of lithium metal anodes, wherein: The solvent is selected from ether-based organic solvents or ester-based organic solvents; The rich-phase dye additive is composed of phenothiazine molecules and azobenzenesulfonic acid molecules. The phenothiazine organic dye molecules include at least one of methylene blue, N-methyl-N-3H-benzothiazine-3-methylene-methylamine, 1,9-dimethylmethylene blue, azure A, methylene green, and neomethylene blue N. The azobenzenesulfonic acid organic dye molecules include sodium 4-dimethylaminoazobenzene-4'-sulfonate (methyl orange) and 4-diethyl... Sodium aminoazobenzene-4'-sulfonate, sodium 4-dibutylaminoazobenzene-4'-sulfonate, sodium 2-[4-(dimethylamino)phenylazo]benzoate, sodium 2-[4-(diethylamino)phenylazo]benzoate, sodium 2-[4-(dipropylamino)phenylazo]benzoate, sodium Acid Orange 7, Acid Orange 10, Acid Red 9, Acid Red 88, Sunset Yellow, Medium Black 17, Medium Black 3, Crocus Orange G, and Alizarin Violet.

[0007] As a further preferred embodiment of the present invention, the molar ratio of phenothiazine molecules to azobenzenesulfonic acid molecules in the rich phase dye additive is 1:0.5~1.5.

[0008] As a further preferred embodiment of the present invention, the lithium salt concentration in the electrolyte is 0.5-3 mol / L. -1 .

[0009] As a further preferred embodiment of the present invention, the lithium salt is at least one of lithium hexafluorophosphate, lithium perchlorate, lithium bis(fluoroimide), lithium bis(trifluoromethanesulfonylimide), lithium trifluoromethanesulfonate, lithium bis(oxalateborate), and lithium difluorooxalateborate.

[0010] As a further preferred embodiment of the present invention, the ether organic solvent is at least one selected from ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, 1,3-dioxolane, tetrahydrofuran, and 1,4-dioxane; the ester organic solvent is at least one selected from ethylene carbonate, fluoroethylene carbonate, vinylene carbonate, propylene carbonate, butene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, methyl formate, methyl acetate, methyl butyrate, ethyl propionate, ethyl butyrate, butyl acetate, methyl propionate, propyl butyrate, trimethyl phosphate, triethyl phosphate, vinyl sulfite, propylene sulfite, and diethyl sulfite.

[0011] As a further preferred embodiment of the present invention, the electrolyte comprises LiTFSI, 1,3-dioxolane, ethylene glycol dimethyl ether, methylene blue, and methyl orange, wherein the molar ratio of LiTFSI, 1,3-dioxolane, and ethylene glycol dimethyl ether is 1.0:7.05:4.8; the molar ratio of methylene blue to methyl orange is 1:1, and the total amount added to the electrolyte is 0.25~2.0 mg / mL. -1 .

[0012] As a further preferred embodiment of the present invention, the electrolyte comprises LiPF6, ethylene carbonate, diethyl carbonate, methyl ethyl carbonate, methylene blue, and methyl orange, wherein the molar ratio of LiPF6, ethylene carbonate, diethyl carbonate, and methyl ethyl carbonate is 1.0:5.0:3.2:2.75; the molar ratio of methylene blue to methyl orange is 1:1, and the total amount added to the electrolyte is 0.25~2.0 mg / mL. -1 .

[0013] According to a second aspect of the present invention, the present invention also provides a method for preparing a lithium battery electrolyte that reduces lithium metal anode polarization, comprising the following steps: S1. Mix lithium salt with solvent to prepare a basic electrolyte, wherein the solvent is selected from ether-based organic solvents or ester-based organic solvents; S2. Add the rich phase dye additive to the base electrolyte and mix thoroughly to obtain a lithium battery electrolyte that reduces the polarization phenomenon of lithium metal negative electrode. The rich phase dye additive is composed of phenothiazine molecules and azobenzenesulfonic acid molecules.

[0014] According to a third aspect of the present invention, the present invention also provides the application of the lithium battery electrolyte described in the first aspect in the preparation of lithium metal batteries that reduce the polarization phenomenon of lithium metal negative electrodes.

[0015] According to a fourth aspect of the present invention, the present invention also provides a lithium metal battery comprising the lithium battery electrolyte described in the first aspect.

[0016] This invention utilizes a phase-rich additive composed of phenothiazine and azobenzenesulfonic acid molecules. In the electrolyte, positively charged phenothiazine cationic dye molecules and negatively charged azobenzenesulfonic acid anionic dye molecules form an "ion-pair adsorption layer" structure through electrostatic attraction. This ionic structure reduces the self-charge repulsion of the molecules, allowing them to co-adsorb more tightly and orderly onto the lithium anode surface, thus constructing a denser physical barrier. Compared to single-phase dye molecule additives, the co-adsorption-formed mixed adsorption layer is denser and more ordered than a single component, and can more effectively isolate the electrolyte from direct contact with lithium metal, suppressing side reactions and significantly reducing the interfacial polarization voltage. Simultaneously, the phase-rich dye ion-pair structure alters the solvation environment around lithium ions, providing multiple sites for ion desolvation, synergistically reducing the desolvation barrier, homogenizing the interfacial electric field, and resulting in a more uniform current density distribution on the electrode surface. Furthermore, this ion-pair structure can promote lithium salt dissociation and ion transport. The polar groups in the compound additives can interact with lithium salt anions, promoting lithium salt dissociation, promoting the dissociation of electrolyte cations and anions, and increasing the migration rate of lithium ions. Attached Figure Description

[0017] The present invention will now be described in further detail with reference to the accompanying drawings and specific embodiments.

[0018] Figure 1 The diagram shows the cycle test results of symmetrical batteries containing ether-based electrolytes with different additives in Example 1 and Comparative Examples 1-3.

[0019] Figure 2 The diagram shows the cycle test results of symmetric batteries containing ester-based electrolytes with different additives in Example 6 and Comparative Examples 6-7.

[0020] Figure 3 The graph shows the exchange current density performance of different ether-based electrolyte systems (Example 2 and Comparative Examples 1-3).

[0021] The objectives, features, and advantages of this invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation

[0022] The specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are for illustration and explanation only and are not intended to limit the present invention.

[0023] Unless otherwise defined, the technical terms used in the following embodiments have the same meanings as commonly understood by those skilled in the art to which this invention pertains. Unless otherwise specified, the experimental reagents used in the following embodiments are conventional biochemical reagents; and the experimental methods described are conventional methods.

[0024] Example 1 This embodiment provides an ether-based electrolyte for improving the electrochemical performance of lithium metal batteries, and the preparation method includes: S1 is prepared by uniformly mixing LiTFSI, 1,3-dioxolane (DOL), and dimethyl ethylene glycol (DME), wherein the molar amounts of LiTFSI, DOL, and DME are 1.0, 7.05, and 4.8, respectively, to form an ether-based electrolyte system. S2, based on a total addition amount of 0.25 mg / mL of rich-phase dye additives. -1 Methylene blue and methyl orange, as additives, were slowly added to the electrolyte system at a molar ratio of 1:1. The mixture was stirred at room temperature for 30 minutes to ensure that the rich phase dye molecules were fully and uniformly dissolved in the electrolyte system, thus preparing the target electrolyte.

[0025] Example 2 The only difference from Example 1 is that the total amount of the rich phase dye additive added is 0.5 mg / mL. -1 The rest is the same as in Example 1.

[0026] Example 3 The only difference from Example 1 is that the total amount of the rich phase dye additive added is 1.0 mg / mL. -1 The rest is the same as in Example 1.

[0027] Example 4 The only difference from Example 1 is that the total amount of the rich phase dye additive added is 2.0 mg / mL. -1 The rest is the same as in Example 1.

[0028] Example 5 The only difference from Example 1 is that the rich phase dye additive is replaced with azure A and methyl orange (molar ratio 1:1), otherwise it is the same as Example 1.

[0029] Example 6 This embodiment provides an ester-based electrolyte for improving the electrochemical performance of lithium metal batteries, the preparation method of which includes: S1 is prepared by uniformly mixing LiPF6, ethylene carbonate (EC), diethyl carbonate (DEC), and methyl ethyl carbonate (EMC), with the molar amounts of LiPF6, EC, DEC, and EMC being 1.0, 5.0, 3.2, and 2.75, respectively, to form an ester-based electrolyte system. S2, based on a total addition amount of 0.25 mg / mL of rich-phase dye additives. -1 Methylene blue and methyl orange, as additives, were slowly added to the electrolyte system at a molar ratio of 1:1. The mixture was stirred at room temperature for 30 minutes to ensure that the rich phase dye molecules were fully and uniformly dissolved in the electrolyte system, thus preparing the target electrolyte.

[0030] Example 7 The only difference from Example 6 is that the rich phase dye additive is replaced with azure A and methyl orange (molar ratio 1:1), otherwise it is the same as Example 6.

[0031] Comparative Example 1 As a control experiment for Examples 1-5, a conventional ether electrolyte without additives is provided, in which the molar amounts of LiTFSI, DOL, and DME are 1.0, 7.05, and 4.8, respectively; the only difference between this electrolyte and Examples 1-5 is that no phase-rich dye molecule additive is added.

[0032] Comparative Example 2 As a control experiment for Examples 1-4, an ether electrolyte containing only a single-phase dye additive is provided. The molar amounts of LiTFSI, DOL, and DME in this electrolyte are 1.0, 7.05, and 4.8, respectively. The only difference between this electrolyte and Examples 1-4 is that in step S2, only the single-phase dye molecular additive methyl orange is added, and the amount added is the same as the amount of methyl orange component added in Example 1.

[0033] Comparative Example 3 As a control experiment for Examples 1-4, an ether electrolyte containing only a single-phase dye additive is provided. The molar amounts of LiTFSI, DOL, and DME in this electrolyte are 1.0, 7.05, and 4.8, respectively. The only difference between this electrolyte and Examples 1-4 is that in step S2, only the single-phase dye molecular additive methylene blue is added, and the amount added is the same as the amount of methylene blue component added in Example 1.

[0034] Comparative Example 4 As a control experiment for Examples 1-4, an ether electrolyte containing only single-phase dye additives is provided. The molar amounts of LiTFSI, DOL, and DME in this electrolyte are 1.0, 7.05, and 4.8, respectively. The only difference between this electrolyte and Examples 1-4 is that in step S2, only the single-phase dye molecular additive methyl orange is added, and the amount added is the same as the total amount of additives in Example 1.

[0035] Comparative Example 5 As a control experiment for Examples 1-4, an ether electrolyte containing only single-phase dye additives is provided. The molar amounts of LiTFSI, DOL, and DME in this electrolyte are 1.0, 7.05, and 4.8, respectively. The only difference between this electrolyte and Examples 1-4 is that in step S2, only the single-phase dye molecular additive methylene blue is added, and the amount added is the same as the total amount of additives in Example 1.

[0036] Comparative Example 6 As a control experiment for Examples 6-7, a conventional ester electrolyte without additives is provided. The molar amounts of LiPF6, EC, DEC, and EMC in this electrolyte are 1.0, 5.0, 3.2, and 2.75, respectively. The difference from Examples 6-7 is that the rich phase dye molecule additive is not added.

[0037] Comparative Example 7 As a control experiment for Examples 6-7, a traditional ester electrolyte containing only single-phase dye additives is provided. The molar amounts of LiPF6, EC, DEC, and EMC in this electrolyte are 1.0, 5.0, 3.2, and 2.75, respectively. The difference from Examples 6-7 is that only the single-phase dye molecular additive methyl orange is added in step S2, and the amount added is the same as that of methyl orange in Example 6.

[0038] Comparative Example 8 As a control experiment for Examples 6-7, a traditional ester electrolyte containing only a single-phase dye additive was provided. The molar amounts of LiPF6, EC, DEC, and EMC in this electrolyte were 1.0, 5.0, 3.2, and 2.75, respectively. The difference from Examples 6-7 is that only the single-phase dye molecular additive methylene blue was added in step S2, and the amount added was the same as that of methylene blue in Example 6.

[0039] The electrolytes prepared in the above examples and comparative examples were used as samples to reduce the polarization of lithium metal anodes for battery assembly and testing. The addition amount of all electrolyte samples was 60 μL. For anode performance testing and characterization, the cyclic electrochemical cycle characteristics, Tafel test, and ion transference number test of the lithium anode were performed by assembling Li|Li symmetric battery structures. All the batteries prepared above used Celgard microporous polymer PP membranes as separators, and the anodes were all unmodified lithium metal wafers. Battery assembly was carried out in a glove box with water and oxygen contents of less than 0.1 ppm.

[0040] Performance testing and results analysis: This invention achieves this by adding phase-rich dye molecules to the conventional electrolyte of lithium batteries, such as... Figure 1 As shown, when the electrolyte solvent is an ether molecule, the current density is as high as 10 mA cm⁻¹. -2 Deposition capacity is 5 mAh cm⁻¹ -2Under extremely harsh testing conditions, the examples exhibited smaller polarization voltages than the comparative examples. Table 1 shows the statistical analysis of the absolute values ​​of polarization voltage fluctuations during the first five cycles. The absolute value of polarization voltage fluctuations in the symmetrical battery assembled using Example 1 was lower than that in Comparative Examples 1-3. Comparative Example 1 had the largest absolute value of polarization voltage fluctuations, while Comparative Examples 2 and 3 had smaller absolute values ​​of polarization voltage fluctuations than Comparative Example 1. This indicates that the single-phase dye molecule additive can delay the occurrence of severe polarization of the lithium metal anode to a certain extent. Example 1, with its smaller absolute value of polarization voltage fluctuations than Comparative Examples 2-3, demonstrates the synergistic inhibitory effect of the phase-rich dye additive on the polarization phenomenon of the lithium metal anode.

[0041] Using the polarization voltage of the symmetrical cell exceeding 2 V for the first time as the criterion for severe polarization, the cycle time required for each sample to reach severe polarization was statistically analyzed. It was found that Comparative Example 1 experienced a sudden voltage increase after 6.43 h of cycling, proving that severe polarization occurred in the lithium anode during a large operating current. Comparative Examples 2 and 3 reached severe polarization in 8.26 h and 10.39 h, respectively, indicating that the single-phase dye additives in the comparative examples could prolong the cycle time for severe polarization in the symmetrical cell of the ether-based electrolyte system. In contrast, Example 1 did not reach severe polarization even after more than 20 h of cycling, demonstrating the excellent physical barrier effect of the denser mixed adsorption layer formed by its "ion-pair adsorption layer" structure on the lithium anode.

[0042] Table 1. Absolute values ​​of polarization voltage fluctuations in the first five cycles When the electrolyte solvent is changed from an ether solvent to an ester solvent, such as Figure 2 As shown, the phase-rich dye additive molecules can also reduce the polarization phenomenon of the lithium anode. The absolute values ​​of the polarization voltage fluctuations in Example 6 are all smaller than those in Comparative Examples 6-8. Furthermore, since ester organic solvents react more readily with lithium metal than ether molecules, severe polarization occurs in a shorter time under harsh test conditions. Comparative Example 6 exhibits severe polarization after only 4.46 hours of cycling. Although Comparative Examples 7 and 8 extend the time to severe polarization to approximately 9.5 hours, they still do not have the same inhibitory effect on the polarization phenomenon at the anode interface as Example 6.

[0043] The lithium-ion transference number of the negative electrode was tested, as shown in Table 2. It was found that the transference numbers of Examples 1-5 were all greater than that of Comparative Example 1. This indicates that the ion pairs formed by the positively charged phenothiazine cations and the negatively charged azobenzenesulfonic acid anions in the electrolyte through electrostatic attraction act as additional ion transport carriers, promoting lithium-ion transport and enhancing its transport kinetics. Among Examples 1-4, Example 2 exhibited the highest transference number, indicating that with a suitable amount of enriched phase additive (0.5 mg / mL)...-1 Under these conditions, a dense, molecularly-rich passivation layer can be constructed on the negative electrode surface through surface co-adsorption, which can maximize the homogeneous distribution of ions and reduce the polarization of the negative electrode. When the amount added is insufficient, a dense, molecularly-rich passivation layer cannot be constructed on the negative electrode surface; when the amount added is too large, the improvement in electrode activity is limited, which is related to the excessive adsorption and accumulation of inactive organic molecules on the negative electrode surface, hindering ion transport at the interface.

[0044] Furthermore, a comparison between Example 1 and Comparative Examples 4-5 shows that even if the amount of single-phase additive added to the electrolyte system is comparable to that of rich-phase additive, its effect on improving lithium-ion migration efficiency is still very limited.

[0045] By comparing Examples 1 and 5, and Examples 6 and 7, it can be shown that the methylamine group on the phenothiazine group has a more suitable ionic interaction with the sulfonic acid anion of methyl orange, thereby promoting the migration of lithium ions.

[0046] Table 2. Lithium-ion transference number The electrochemical processes of different samples were characterized using Tafel testing, such as... Figure 3 As shown, the negative electrode polarization curves changed significantly after adding single-phase and rich-phase dye additives to the electrolyte. The exchange current densities of Examples 2 and 2-3 were higher than those of Comparative Example 1, indicating that the adsorption of dye molecules on the negative electrode surface altered the chemical environment of the lithium metal negative electrode interface, maintaining surface stability and reducing electrode polarization. Example 2 exhibited the highest exchange current density value, exceeding that of Comparative Examples 2-3. This demonstrates that, compared to single-phase dye additives, the cation-anion pair structure formed by the rich-phase dye molecules of this invention preferentially adsorbs at the protrusions on the lithium surface, more effectively shielding local strong electric fields and resulting in a more uniform current density distribution on the electrode surface. This promotes uniform deposition of lithium ions at lower overpotentials. Simultaneously, the formation of ion pairs alters the solvation environment surrounding lithium ions. The simultaneous presence of electron-rich phenothiazine rings and highly polar sulfonic acid groups in the adsorption layer effectively promotes the desolvation process of lithium ions. This synergistic effect lowers the desolvation energy barrier, thereby increasing the activity of the redox reaction at the lithium negative electrode.

[0047] While specific embodiments of the present invention have been described above, those skilled in the art should understand that these are merely illustrative examples, and various changes or modifications can be made to these embodiments without departing from the principles and essence of the present invention. The scope of protection of the present invention is defined only by the appended claims.

Claims

1. A lithium battery electrolyte for reducing lithium metal anode polarization, characterized in that, The electrolyte comprises lithium salt, solvent, and a concentration of 0.25-2.0 mg / mL. -1 A phase-rich dye additive used to reduce the polarization phenomenon of lithium metal anodes, wherein: The solvent is selected from ether-based organic solvents or ester-based organic solvents; The rich-phase dye additive is composed of phenothiazine molecules and azobenzenesulfonic acid molecules. The phenothiazine organic dye molecules include at least one of methylene blue, N-methyl-N-3H-benzothiazine-3-methylene-methylamine, 1,9-dimethylmethylene blue, azure A, methylene green, and neomethylene blue N. The azobenzenesulfonic acid organic dye molecules include sodium 4-dimethylaminoazobenzene-4'-sulfonate and 4-diethylamino... Sodium azobenzene-4'-sulfonate, sodium 4-dibutylaminoazobenzene-4'-sulfonate, sodium 2-[4-(dimethylamino)phenylazo]benzoate, sodium 2-[4-(diethylamino)phenylazo]benzoate, sodium 2-[4-(dipropylamino)phenylazo]benzoate, sodium Acid Orange 7, Acid Orange 10, Acid Red 9, Acid Red 88, Sunset Yellow, Medium Black 17, Medium Black 3, Crocus Orange G, and Alizarin Violet.

2. The lithium battery electrolyte for reducing lithium metal anode polarization according to claim 1, characterized in that, The molar ratio of phenothiazine molecules to azobenzenesulfonic acid molecules in the rich phase dye additive is 1:0.5~1.

5.

3. The lithium battery electrolyte for reducing lithium metal anode polarization according to claim 1, characterized in that, The lithium salt concentration in the electrolyte is 0.5-3 mol / L. -1 .

4. The lithium battery electrolyte for reducing lithium metal anode polarization according to claim 1, characterized in that, The lithium salt is at least one of lithium hexafluorophosphate, lithium perchlorate, lithium bis(fluoroimide), lithium bis(trifluoromethanesulfonylimide), lithium trifluoromethanesulfonate, lithium bis(oxalateborate), and lithium difluorooxalateborate.

5. The lithium battery electrolyte for reducing lithium metal anode polarization according to claim 1, characterized in that, The ether organic solvent is at least one selected from ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, 1,3-dioxolane, tetrahydrofuran, and 1,4-dioxane; the ester organic solvent is at least one selected from ethylene carbonate, fluoroethylene carbonate, vinylene carbonate, propylene carbonate, butene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, methyl formate, methyl acetate, methyl butyrate, ethyl propionate, ethyl butyrate, butyl acetate, methyl propionate, propyl butyrate, trimethyl phosphate, triethyl phosphate, vinyl sulfite, propylene sulfite, and diethyl sulfite.

6. The lithium battery electrolyte for reducing lithium metal anode polarization according to claim 1, characterized in that, The electrolyte comprises LiTFSI, 1,3-dioxolane, ethylene glycol dimethyl ether, methylene blue, and methyl orange, wherein the molar ratio of LiTFSI, 1,3-dioxolane, and ethylene glycol dimethyl ether is 1.0:7.05:4.8; the molar ratio of methylene blue to methyl orange is 1:1, and the total amount added to the electrolyte is 0.25~2.0 mg / mL. -1 .

7. The lithium battery electrolyte for reducing lithium metal anode polarization according to claim 1, characterized in that, The electrolyte comprises LiPF6, ethylene carbonate, diethyl carbonate, methyl ethyl carbonate, methylene blue, and methyl orange, wherein the molar ratio of LiPF6, ethylene carbonate, diethyl carbonate, and methyl ethyl carbonate is 1.0:5.0:3.2:2.75; the molar ratio of methylene blue to methyl orange is 1:1, and the total amount added to the electrolyte is 0.25~2.0 mg / mL. -1 .

8. The method for preparing a lithium battery electrolyte for reducing lithium metal anode polarization according to any one of claims 1-7, characterized in that, Includes the following steps: S1. Mix lithium salt with solvent to prepare a basic electrolyte, wherein the solvent is selected from ether-based organic solvents or ester-based organic solvents; S2. Add the rich phase dye additive to the base electrolyte and mix thoroughly to obtain a lithium battery electrolyte that reduces the polarization phenomenon of lithium metal negative electrode. The rich phase dye additive is composed of phenothiazine molecules and azobenzenesulfonic acid molecules.

9. The application of the lithium battery electrolyte according to any one of claims 1-7 in the preparation of lithium metal batteries that reduce the polarization phenomenon of lithium metal negative electrode.

10. A lithium metal battery, characterized in that, Includes the lithium battery electrolyte according to any one of claims 1-7.